2018
DOI: 10.1080/00071668.2018.1483575
|View full text |Cite
|
Sign up to set email alerts
|

The effects of phytase and xylanase supplementation on performance and egg quality in laying hens

Abstract: 1. The aim of this study was to evaluate the effects of phytase and xylanase and their interaction on laying hen performance, egg quality, phosphorus (P) digestibility, phytate breakdown, volatile fatty acid (VFA) production and peptide YY concentration. 2. Two hundred and forty hens were allocated to cages at 22 weeks of age based on a 3 × 2 arrangement with phytase (0, 300 or 1500 FTU/kg) and xylanase (0 or 12 000 BXU/kg) as factors. 3. Phytase increased hen-day production (P < 0.05), daily egg mass (P < 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 42 publications
3
13
2
Order By: Relevance
“…(2012) noted that feed consumption of hens fed wheat-based diets in their studies were approximately 111 and 88 g/hen per day, respectively. However, the values in this study were lower than those presented by Taylor et al. (2018) , who noted consumption of 124 to 126 g/hen per day when feeding xylanase in wheat-based diets, although FCR and hen-day-production were comparatively better (8% and 12%, respectively) in the current study.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…(2012) noted that feed consumption of hens fed wheat-based diets in their studies were approximately 111 and 88 g/hen per day, respectively. However, the values in this study were lower than those presented by Taylor et al. (2018) , who noted consumption of 124 to 126 g/hen per day when feeding xylanase in wheat-based diets, although FCR and hen-day-production were comparatively better (8% and 12%, respectively) in the current study.…”
Section: Discussioncontrasting
confidence: 95%
“…Xylanase can hydrolyze long-chain arabinoxylans into small-chain xylo-oligomers to improve nutrient digestibility, but it has been proven that xylanase has a quadratic correlation with digesta viscosity. In this study the supplemental dose was high compared with the low level of sNSP and xylan present in the diet, meaning that the xylanase likely degraded the insoluble NSP into sNSP, uplifting the digesta water holding capacity, therefore slightly reducing dry matter digestibility ( Taylor et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The concentrations of SCFA in the ileum and ceca of laying hens were higher than the concentrations mentioned in previous laying hen research ( Johnson et al, 2008 ; Taylor et al, 2018 ), although the procedure of SCFA analysis including the extraction method was similar across the experiments. It might be associated with the difference in the age of laying hens, the composition of the diets and the rearing environment that eventually affects the microbial population in the digestive tract of the birds.…”
Section: Discussioncontrasting
confidence: 70%
“…According to the authors, phytase makes complexed phosphorus available to phytic acid, improving its utilization, as well as other nutrients (calcium, iron, manganese, zinc, protein, and metabolizable energy) previously unavailable due to the complexation of the enzyme with phytate. Taylor et al (2018) observed a positive interaction between phytase and xylanase for the feed conversion ratio. The improvement in this ratio is attributed to the increase in nutrient availability in the substrate degraded by phytase.…”
Section: Resultsmentioning
confidence: 90%